Placental Nutrient Transport in Gestational Diabetic Pregnancies - Castillo-Castrejon, Marisol; Powell, Theresa L. (Frontiers in Endocrinology, 2017)
Maternal obesity during pregnancy is rising and is associated with increased risk of developing gestational diabetes mellitus (1). Fetal growth is determined by the maternal nutrient supply and placental nutrient transfer capacity. GDM-complicated pregnancies are more likely to be complicated by fetal overgrowth or excess adipose deposition in utero. Infants born from GDM mothers have an increased risk of developing cardiovascular and metabolic disorders later in life. Diverse factors such as ethnicity, age, fetal sex, clinical treatment for glycemic control, gestational weight gain, body mass index among others represent a challenge for studying underlying mechanisms in GDM subjects. Determining the individual roles of glucose intolerance, obesity and other factors on placental function and fetal growth remains a challenge. This review provides an overview of changes in placental macronutrient transport observed in human pregnancies complicated by GDM. Improved knowledge and understanding of the alterations in placenta function that lead to pathological fetal growth will allow for development of new therapeutic interventions and treatments to improve pregnancy outcomes and lifelong health for the mother and her children.